The meso-failure mechanism of lightweight concrete simulated by the phase field method. Issue 10 (11th June 2021) - Wang, Jichang; Guo, Xiaoming
Abstract : Purpose: A mesoscopic phase field (PF) model is proposed to simulate the meso-failure process of lightweight concrete. Design/methodology/approach: The PF damage model is applied to the meso-failure process of lightweight concrete through the ABAQUS subroutine user-defined element (UEL). And the improved staggered iteration scheme with a one-pass procedure is used to alternately solve the coupling equations. Findings: These examples clearly show that the crack initiation of the lightweight concrete specimens mainly occurs in the ceramsite aggregates with weak strength, especially in the larger aggregates. The crack propagation paths of the specimens with the same volume fraction of light aggregates are completely different, but the crack propagation paths all pass through the ceramsite aggregates near the cracks. The results also showed that with the increase in the volume fractions of the aggregates, the slope and the peak loads of the force-deflection (F-d) curves gradually decrease, the load-bearing capacity of the lightweight concrete specimens decreases, and crack branching and coalescence are less likely during crack propagation. Originality/value: The mesostructures with a mortar matrix, aggregates and an interfacial transition zone (ITZ) are generated by an automatic generation and placement program, thus incorporating the typical three-phase characteristics of lightweight concrete into the PF model.